The adoption of international travel measures during the first year of the COVID-19 pandemic: a descriptive analysis - Karen A. Grépin; Mingqi Song; Julianne Piper; Catherine Z. Worsnop; Kelley Lee (BMC, 2024)
Abstract Objective To describe the adoption of international travel measures during the first year of the COVID-19 pandemic. Methods To comprehensively analyze the measures adopted, we constructed a dataset based on the WHO's Public Health and Social Measures (PHSM) database, which covered 252 countries, territories, or other areas (CTAs), including all 194 WHO Member States, from December 31, 2019, to December 31, 2020. We examined the adoption of measures by type, over time, and by the implementing and targeted CTA, including their levels of income. Findings We identified 11,431 international travel measures implemented during the first year of the pandemic. The adoption of measures was rapid and widespread: over 60% of Member States had adopted a travel measure before the WHO declared COVID-19 a Public Health Emergency of International Concern on January 30, 2020. Initially, health screening and travel restrictions were the most adopted measures; however, quarantine and testing became more widely adopted over time. Although only a small portion of the total measures adopted constituted full border closure, approximately half of all Member States implemented this measure. Many travel measures targeted all CTAs but were unlikely to have been adopted universally enough to provide public health benefits. Low-income countries relied more on more universal measures, including full border closure, and were slower in scaling up testing compared to higher-income countries. Conclusion The adoption of international travel measures during the first year of the COVID-19 pandemic varied across jurisdictions and over time. Lower-income countries used a different mix and scaled-up measures slower than higher-income countries. Understanding what measures were used is crucial for assessing their effectiveness in controlling the spread of COVID-19, reviewing the usefulness of the International Health Regulations, and informing future pandemic preparedness and response activities.